Sejarah Pemikiran Diplomatik: Konflik Indonesia-Belanda Pada Kmb Dan Isu Yang Belum Terselesaikan - Epa Juliarni; Mestika Zed (Jurnal Kronologi, 2019)
After the proclamation of Indonesian independence in 1945, Indonesia was not yet fully independent. The Dutch returned and wanted to dominate Indonesia. There was a conflict between Indonesia and Dutch caused them confront to the negotiating table. Through the Round Table Conference, Indonesia was recognized as an independent country both de facto and de jure. The full independence was obtained with several agreements whereas other was harmed. The agreement is about the problems of debt, the Union, and West Irian. These problems caused controversy at later time. The Union problem in 1956 which Indonesia unilaterally canceled the Indonesia-Dutch Union. Also, the West Irian problem between the Indonesia and Dutch conflict was difficult to resolve. Based on the results of researches, the emergence of the problem of West Irian was motivated by different views in assessing the status of West Irian. It refers to the conviction of each country to entitled West Irian into its territory. Finally, the problem of West Irian could be resolved through act of free choice (PEPERA), but it caused new complex problems. The problems were the Free Papua Organization (OPM), the Freeport case and Special Autonomy (Otsus).